2018
DOI: 10.2340/00015555-2969
|View full text |Cite
|
Sign up to set email alerts
|

CDKN2A/CDK4 Status in Greek Patients with Familial Melanoma and Association with Clinico-epidemiological Parameters

Abstract: Approximately 5-10% of melanoma cases occur in a familial context. CDKN2A/CDK4 were the first high-penetrance melanoma genes identified. The aims of this study were to evaluate CDKN2A/CDK4 variants in Greek familial melanoma patients and to correlate the mutational status with specific clinico-epidemiological characteristics. A cross-sectional study was conducted by genotyping CDKN2A/CDK4 variants and selected MC1R polymorphisms in 52 melanoma-prone families. Descriptive statistics were calculated and comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…The results showed that case and control groups did not display in vivo 35 A study analyzed an Australian population of 1,109 melanoma patients, but no CDK4 variants were found (18). However, prior studies reported that CDK4 variants frequencies are approximately between 2-15% in Greek (19), Latvian (20), and other populations (5). Germline variants (500C>G and 540C>T) in the CDKN2A 3'UTR gene have been found in approximately 12-31% of cutaneous melanomas and healthy controls, respectively (21)(22)(23), as well as associated with a risk of developing other types of cancer (24).…”
Section: Discussionmentioning
confidence: 94%
“…The results showed that case and control groups did not display in vivo 35 A study analyzed an Australian population of 1,109 melanoma patients, but no CDK4 variants were found (18). However, prior studies reported that CDK4 variants frequencies are approximately between 2-15% in Greek (19), Latvian (20), and other populations (5). Germline variants (500C>G and 540C>T) in the CDKN2A 3'UTR gene have been found in approximately 12-31% of cutaneous melanomas and healthy controls, respectively (21)(22)(23), as well as associated with a risk of developing other types of cancer (24).…”
Section: Discussionmentioning
confidence: 94%
“…p.V126D variant has been previously detected in North American patients with familiar history of melanoma; however, in this study, the variant was detected in patients and healthy controls without familiar history of melanoma [ 39 ]. Similarly, the p.A148T variant was detected in patients and controls; this variant has been reported in the different population as Brazilian [ 40 ], Australian [ 18 ], Israeli [ 41 ], and Greek [ 5 ].…”
Section: Discussionmentioning
confidence: 83%
“…The incidence and mortality rate has increased in recent years, with 26% in the mortality rates as reported by Globocan [ 2 , 3 ]. The etiology of melanoma is driven by the interaction between environmental factors (UV radiation) [ 4 ]; phenotypic features (red or blond hair, blue or green eyes, light skin phototypes, freckles, multiple melanocytic nevi, and the presence of nevus clinically atypical) [ 5 ]; and genotypic features such as mutations, single nucleotide polymorphisms (SNPs), and family history of melanoma [ 6 ]. SNPs have been used as markers to identify genetic susceptibility to develop any disease [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the low number of Greek families might have contributed to amplifying these differences, the mutation rates identified in our families are consistent with those previously reported in each country, excluding reports of higher frequency due to founder effects. 15,[43][44][45][46][47][48] A higher impact of genetic risk factors has been suggested in the Greek low incidence population. 48 A high number of affected members, early age at diagnosis and MPM are considered predictors of CDKN2A variation.…”
Section: Discussionmentioning
confidence: 99%